Role of highly sensitive nucleic acid amplification testing for plasma cytomegalovirus DNA load in diagnosis of cytomegalovirus gastrointestinal disease among kidney transplant recipients - Touchapong Taksinwarajarn (2022)
Background: High plasma cytomegalovirus (CMV) DNA load is generally associated with CMV tissue-invasive disease in solid organ transplant recipients. However, some tissue-invasive diseases, especially CMV gastrointestinal (GI) disease, have undetectable to very low plasma CMV DNA loads. Highly sensitive nucleic acid amplification testing (NAAT) has been increasingly used to quantify low-level CMV DNA loads. Our primary objective was to investigate the epidemiology of CMV GI disease and evaluate the validity of plasma CMV NAAT for the diagnosis of CMV GI disease in kidney transplant (KT) recipients. Methods: We conducted a retrospective study of all KT recipients who developed CMV GI disease from January 2016 to December 2018. Plasma CMV DNA load was measured using real-time PCR. The cut-off value of plasma CMV DNA load for diagnosing and risk factors of CMV GI disease were analyzed. Results: A total 17 (3.4%) cases of CMV GI disease occurred in 494 KT recipients. Fifteen (88%) patients had CMV D + /R + serostatus. Fourteen (82%) patients developed CMV GI disease within 6 months after KT. Plasma CMV DNA loads were detectable in all (100%) patients with a median load 11,102 (IQR 2,935-107,160) IU/ml. A plasma CMV DNA load of 4,063 IU/ml was established as al cut-off for diagnosing CMV GI disease (AUC 0.74, sensitivity 76.5%, specificity 70%, PPV 68, NPV 78). In multivariate analysis, prolonged cold ischemic time (HR 1.14, 95% CI 1.05-1.23, P =.002) and CMV D + /R - serostatus (HR 9.31, 95% CI 2.12-40.74, P =.003) were associated with CMV GI disease. Conclusions: Using highly sensitive NAAT could potentially assist in the diagnosis of CMV GI disease in a CMV D + /R + serostatus setting. KT recipients with CMV seromismatch and prolonged cold ischemic time are at higher risk of CMV GI disease.